HIV Self-Testing: A Discussion on the Benefits, Limitations, and Implications for Public Health with a Focus on Poland - Aleksandra Kozieł; Igor Domański; Aleksandra Szymczak; Tomasz Dudzik; Brygida Knysz; Bartosz Szetela (Diagnostics)
Background/Objectives: A late HIV diagnosis represents a significant public health concern in Poland, with approximately 50% of patients being identified as late presenters (LPs), resulting in the delayed initiation of treatment. This study assesses the potential of HIV self-testing (HIVST) to enhance early detection, particularly among heterosexual individuals, and evaluates its advantages and limitations within the Polish context. Methods: This study examines the advantages and disadvantages of HIVST by analyzing data from various studies. It focuses on the acceptability, sensitivity, and specificity of HIVST, comparing blood-based and oral fluid-based tests. Moreover, the economic impact and potential public health benefits of HIVST in Poland are evaluated. Results: HIVST is well-accepted, especially among key populations; it can reduce stigma and enhance privacy. The results of studies conducted in Poland indicate that heterosexuals are more inclined to use self-testing methods than traditional diagnostic procedures. On the other hand, HIVST has the potential for false-negative results due to the serological window and the possibility of missed diagnoses of other sexually transmitted infections (STIs). Moreover, the cost of HIVST remains a significant barrier, as it is not publicly funded in Poland. Conclusions: Despite its limitations, HIVST offers a number of significant benefits, including increased rates of testing and earlier detection, which could prove vital in reducing the transmission of HIV in Poland. This study proposes that increased funding, the integration of HIVST into public health strategies, and further research to enhance its implementation, alongside education and support for its effective use, should be prioritized.